2017
DOI: 10.1016/j.pbiomolbio.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of titin strain on the cardiac slow force response

Abstract: Stretch of myocardium, such as occurs upon increased filling of the cardiac chamber, induces two distinct responses: an immediate increase in twitch force followed by a slower increase in twitch force that develops over the course of several minutes. The immediate response is due, in part, to modulation of myofilament Ca2+ sensitivity by sarcomere length (SL). The slowly developing force response, termed the Slow Force Response (SFR), is caused by a slowly developing increase in intracellular Ca2+ upon sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…It is likely that the decreased passive stiffness would have an effect when the heart muscle is shortening under load that would not be apparent in the isometric contraction 31 . Such changes could be related to disruption of the dynamics of myosin head activation by stretch leading to reduced contractility 32 or alteration of the “slow force response” by modulating of mechanosensitive signalling pathways that affect [Ca 2+ ]i homeostasis and promote apoptosis and fibrosis as observed in our samples 33 . In concert such processes could impair contractility and potentially trigger a DCM phenotype.…”
Section: Discussionmentioning
confidence: 82%
“…It is likely that the decreased passive stiffness would have an effect when the heart muscle is shortening under load that would not be apparent in the isometric contraction 31 . Such changes could be related to disruption of the dynamics of myosin head activation by stretch leading to reduced contractility 32 or alteration of the “slow force response” by modulating of mechanosensitive signalling pathways that affect [Ca 2+ ]i homeostasis and promote apoptosis and fibrosis as observed in our samples 33 . In concert such processes could impair contractility and potentially trigger a DCM phenotype.…”
Section: Discussionmentioning
confidence: 82%
“…31 Recent evidence has suggested that titin may also operate as a stretch-sensitive modifier of active force generation. 33 As an aside, the observation that passive force decreases over the time course of the SFR has recently been attributed to increased titin phosphorylation via the cGMP-PKG activity in response to NO production. 33 As an aside, the observation that passive force decreases over the time course of the SFR has recently been attributed to increased titin phosphorylation via the cGMP-PKG activity in response to NO production.…”
Section: Titinmentioning
confidence: 99%
“…32 This suggestion is supported by studies showing a direct correlation between the active magnitude of the SFR and titin strain. 33 As an aside, the observation that passive force decreases over the time course of the SFR has recently been attributed to increased titin phosphorylation via the cGMP-PKG activity in response to NO production. 34 Titin kinase (A-band) 35 and N2B/N2A (I-band) 36,37 are examples of mechanosensitive regions of titin.…”
Section: Titinmentioning
confidence: 99%
“…B 286: 20190719 mediates these phenomena in cardiac muscle. However, the underlying molecular mechanisms, in particular during long eccentric contractions of myocardium, remain(s) unknown [39,40].…”
Section: Introductionmentioning
confidence: 99%